Nanomaterials-based treatment options for chromium in aqueous environments. (September 2019) - Maitlo, Hubdar Ali; Kim, Ki-Hyun; Kumar, Vanish; Kim, Sumin; Park, Jae-Woo
Abstract: Sustainable development and the restoration of ecosystems are the important goals for civilization. Currently, heavy metal contamination of aquatic environments has become a serious issue. Chromium (Cr) is simultaneously an essential metallic element and one of 20 chemicals posing a maximum threat to living beings. To mitigate that threat, various treatment methods have been developed, including adsorption, electrocoagulation, photoelectrocatalysis, fuel cells, bioremediation, chemical precipitation, ultrafiltration, ion exchange, and co-precipitation. However, selection of the most energy- and cost-efficient wastewater treatment option has proven challenging, as each approach is subject to shortcomings involving energy consumption, treatment capacity, and efficiency. This review describes the potential role of diverse functional nanomaterials (e.g., iron/iron oxide nanoparticles, carbon nanostructures, metal organic frameworks, and their commercial counterparts) in treatment of Cr in aqueous environments with respect to key figure of merits, such as, adsorption capacity, removal efficiency, and partition coefficient. In addition, their performance was compared with the most common treatment options. The results of this study will help determine the most effective and economical options for control of Cr in aquatic environments. Highlights: To date, contamination of heavy metals like Cr in aquatic environments has become a serious issue. To help mitigate Cr pollution, the potential of diverse functional nanomaterials has been assessed. Their performance has been evaluated with respect to key figure of merits such partition coefficient. This review will help determine effective/economical options for the control of Cr in water.